Concentration Dependence of Human and Mouse Aryl Hydrocarbon Receptor Responsiveness to Polychlorinated Biphenyl Exposures: Implications for Aroclor Mixtures - Shi, Hongxue (Xenobiotica, 2019)
1. Aryl hydrocarbon receptor (AhR) ligands, including 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) and polychlorinated biphenyls (PCBs), are endocrine disrupting chemicals associated with nonalcoholic fatty liver disease. This study documents the species-specific differences between mouse (high affinity mAhR) and human AhR (hAhR) activation by PCB congeners and Aroclor mixtures. 2. AhR activation by TCDD or PCBs 77, 81, 114, 114, 126, and 169 was measured using luciferase reporter constructs transfected into either Hepa1c1c7 mouse or HepG2 human liver cell lines. The EC(50) values were lower in Hepa1c1c7 cells than HepG2 cells for all compounds tested except PCB 81. The results for TCDD and PCB 126 were validated in primary human and mouse hepatocytes by measuring CYP1A1 gene transcript levels. 3. Because humans are exposed to PCB mixtures, several mixtures (Aroclors 1254; 1260; and 1260 + 0.1% PCB126 each at 10 μg/ml) were then tested. Neither Aroclor 1254 nor Aroclor 1260 increased luciferase activity by the transfected AhR reporter construct. The Aroclor 1260 + 0.1% PCB 126 mixture induced mAhR-mediated transactivation, but not hAhR activation in cell lines. 4. In summary, significant concentration-dependent differences exist between human and mouse AhR activation by PCBs. Relative effect potencies differed, in some cases, from published toxic equivalency factors.